Part 1: Simple Definition and Calculation of Accuracy, Sensitivity and Specificity - Baratloo, Alireza; Hosseini, Mostafa; Negida, Ahmed; El Ashal, Gehad (Archives of Academic Emergency Medicine, 2018)
Emergency physicians, like other specialists, are faced with different patients and various situations each day. They have to use ancillary diagnostic tools like laboratory tests and imaging studies to be able to manage them. In most cases, numerous tests are available. Tests with the least error and the most accuracy are more desirable. The power of a test to separate patients from healthy ones determines its accuracy and diagnostic value. Therefore, a test with 100% accuracy should be the first choice. This does not happen in reality as the accuracy of a test varies for different diseases and in different situations. For example, the value of D-dimer for diagnosing pulmonary embolism varies based on pre-test probability. It shows high accuracy in low risk patient and low accuracy in high risk ones. The characteristics of a test that reflects the aforementioned abilities are accuracy, sensitivity, specificity, positive and negative predictive values and positive and negative likelihood ratios. In this educational review, we will simply define and calculate the accuracy, sensitivity, and specificity of a hypothetical test.